Preparation method suitable for spherical and flaky silver-coated copper powder
By using amino acids as a single additive, the preparation process of silver-clad copper powder is simplified, and the problems of complexity, pollution, high energy consumption and poor performance in the existing methods are solved, and green, environmentally friendly, low energy consumption and high performance are achieved. Copper powder preparation.
Patent Information
- Application Number
- CN202411530590.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The existing silver-clad copper powder preparation method is complex and requires a variety of additives, which leads to environmental pollution and health risks, and has high energy consumption and poor preparation performance, which limits industrial production. At the same time, it is difficult for traditional methods to prepare sheet-like silver-clad copper powder that meets the needs.
The use of amino acids as a single additive to achieve complexation, dispersion and reduction functions, simplify the preparation process, reduce energy consumption, and is suitable for the preparation of spherical and sheet-like silver-clad copper powder.
It realizes a green and environmentally friendly preparation process, reduces energy consumption and additive usage, improves preparation safety and performance, and can prepare spherical or sheet-like silver-clad copper powder with good versatility.
Smart Images

Figure CN119387581A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of silver-copper micron composite materials, and in particular relates to a method for preparing spherical and flaky silver-coated copper powders. Background Art
[0002] Ag and Cu have high conductivity and are widely used in the fields of electronics, catalysis, sensors, optics and biological devices. However, due to the scarcity of silver in the earth's crust and the easy oxidation of copper, their application is seriously restricted. Therefore, copper-silver composite powder is considered to be an ideal choice for the current electronics industry instead of single copper powder or silver powder.
[0003] There are many methods for preparing copper-silver composite powders, such as electroplating, vacuum process, sputtering, etc. However, due to low efficiency or the need for expensive equipment, the above-mentioned preparation methods are limited and have a negative impact on their industrial application.
[0004] Chemical plating has become the most promising method for synthesizing copper-silver composite powders due to its simplicity, high efficiency and low cost. In the process of chemical plating, it is usually necessary to add additives such as complexing agents, reducing agents, and dispersants to the reaction system. Among them, the addition of complexing agents can avoid the aggregation of silver particles and determine the uniformity of the coating in the final product; in the electro-reduction process driven by the silver-copper potential difference, there is a limit to the thickness of the coating obtained. The addition of reducing agents can adjust the thickness of the coating and make the coating denser. Usually, polymer compounds with long-chain structures are used as dispersants (or stabilizers) to prevent powder agglomeration, such as polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), gelatin, gum arabic, etc. The dispersant is adsorbed on the surface of the powder, and its long-chain structure produces a steric hindrance effect, preventing collisions between powders, thereby reducing agglomeration.
[0005] For example, Zhao et al. used ammonia as a complexing agent and hydrazine hydrate as a reducing agent to prepare silver-coated copper particles. However, due to the + The stability is poor, resulting in uneven silver plating on the surface of the prepared silver-coated copper particles. Lee et al. used oleylamine as a reducing agent, heated the system to 235 ° C under argon protection to prepare nano copper powder, and then added a mixture of AgNO3 and oleylamine into the reaction vessel to prepare silver-coated copper nanoparticles through a replacement reaction.
[0006] In summary, the current preparation method of silver-coated copper powder is relatively complicated and requires the addition of multiple additives. The additives usually involve chemical reagents, which can easily cause environmental pollution and harm the health of workers. In addition, in the process of preparing silver-coated copper powder, it is necessary to heat to a higher temperature and provide additional gas protection, which consumes a lot of energy. At the same time, the prepared silver-coated copper particles also have the problem of poor performance, which limits the industrial production of silver-coated copper powder.
[0007] In addition, with the development of the application field of silver-coated copper powder, new requirements have been put forward for the morphology of silver-coated copper powder. In addition to traditional spherical or quasi-spherical powders, the demand for silver-coated copper powders with flake morphology is increasing. However, due to the larger specific surface area and surface energy of the two-dimensional structure and the more complex surface state, the formation of flake silver-coated copper powder has a complex formation mechanism and energy structure. The preparation method of spherical or quasi-spherical silver-coated copper powder is less versatile. Direct application to the preparation of flake silver-coated copper powder has problems such as poor control of the core-shell structure and poor performance adjustability, and it is impossible to prepare flake silver-coated copper powder with performance that meets the requirements.
[0008] Therefore, it is necessary to provide a preparation method suitable for spherical and flaky silver-coated copper powder, simplify the preparation method of silver-coated copper powder, reduce the use of additives, improve the safety and environmental protection of the preparation method, and reduce energy consumption, so as to prepare silver-coated copper powder with performance that meets the requirements using a simple, efficient, and green preparation method. Summary of the invention
[0009] In order to overcome the problems in the background technology, the present invention uses amino acids as additives to achieve complexation, dispersion, and reduction functions at the same time, reduce the use of additives, and improve the safety and environmental protection of the preparation process. In the preparation process of the present invention, no complex equipment is required, the heating temperature is at a low level, no gas protection is required, it is simple and efficient, and the energy consumption is low.
[0010] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0011] The preparation method comprises the following steps:
[0012] (1) mixing an amino acid solution and a silver nitrate solution to obtain a mixed solution;
[0013] (2) firstly placing the copper micron particle dispersion solution or the copper micron flake dispersion solution under reaction temperature conditions and stirring the solution to make the copper micron particle dispersion solution or the copper micron flake dispersion solution reach the reaction temperature, keeping stirring and the temperature constant, then adding the mixed solution to the copper micron particle dispersion solution or the copper micron flake dispersion solution, reacting for a period of time, and obtaining a silver-coated copper powder stock solution;
[0014] (3) After the silver-coated copper powder stock solution is centrifuged, a solid powder is obtained, and after the solid powder is washed and dried, the silver-coated copper powder is obtained.
[0015] Preferably, in step (2), the reaction temperature is 10-40° C. and the reaction time is 0.5-4 h.
[0016] Preferably, in step (2), the rate of adding the mixed solution is 200 to 1000 μl / min.
[0017] Preferably, the amino acid includes one or more of glycine, L-alanine, L-glutamic acid and valine.
[0018] Preferably, the molar concentration of the amino acid solution is 0.01-0.5 mol / L.
[0019] Preferably, the molar concentration of the silver nitrate solution is 0.01-0.1 mol / L.
[0020] Preferably, in step (1), the molar ratio of silver nitrate to amino acid in the mixed solution is 1:8 to 2:1.
[0021] Preferably, in step (2), the ratio of the amount of the copper micron particle dispersion solution or the copper micron flake dispersion solution to the amount of silver nitrate is 3.5:1 to 9:1.
[0022] Preferably, the specific preparation method of the copper micron particle dispersion solution is: weighing α-cyclodextrin, copper sulfate, and ascorbic acid according to a molar ratio of α-cyclodextrin: copper sulfate: ascorbic acid = 1:20:20 to 1:5:10, dissolving α-cyclodextrin, copper sulfate, and ascorbic acid in deionized water, respectively, to obtain an α-cyclodextrin solution, a copper sulfate solution, and an ascorbic acid solution; pouring the copper sulfate solution into the α-cyclodextrin solution at 60 to 90° C., and then stirring for 15 to 20 minutes, then adding the ascorbic acid solution, and reacting for 0.5 to 2 hours to obtain a copper micron particle stock solution; centrifuging the copper micron particle stock solution to obtain copper micron particles, washing the copper micron particles, and then adding the copper micron particles to ethanol to obtain a copper micron particle dispersion solution;
[0023] The specific preparation method of the copper microsheet dispersion solution is as follows: octadecylamine, copper bromide and glucose are weighed according to a molar ratio of octadecylamine: copper bromide: glucose = 1:1:1 to 5:2:1, and octadecylamine, copper bromide and glucose are respectively dissolved in deionized water to obtain octadecylamine solution, copper bromide solution and glucose solution; the octadecylamine solution is stirred at 50 to 70° C. to form a white emulsion, and then copper bromide is added to the white emulsion, and after continuous stirring for 0.5 h, the glucose solution is added and continued to be stirred to form a blue emulsion; the blue emulsion is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and after reacting at 100 to 130° C. for 8 to 20 h, copper microsheets are obtained, and after washing the copper microsheets, the copper microsheets are added to ethanol to obtain a copper microsheet dispersion solution.
[0024] Preferably, the amino acid solution is prepared by dissolving amino acids in deionized water; and the silver nitrate solution is prepared by dissolving silver nitrate in deionized water.
[0025] Beneficial effects of the present invention:
[0026] 1. In the preparation process of the present invention, only amino acids are added to play the role of complexation, dispersion and reduction. Amino acids themselves will not pollute the environment. At the same time, they are used in the fields of medicine and food and will not cause harm to the human body. Therefore, the preparation process of the present invention is green and environmentally friendly.
[0027] 2. In the preparation process of the present invention, there is no need to use complex instruments and equipment. At the same time, the number of additives is reduced, no gas protection is required, and no special processes such as pH adjustment are required, which are helpful to simplify the preparation process of silver-coated copper powder.
[0028] 3. In the preparation process of the present invention, the reaction system only needs to be heated to a relatively low temperature, and no gas protection is required, which is beneficial to reducing energy consumption in the preparation process.
[0029] 4. The preparation method of the present invention can be applied to the preparation of spherical and flaky silver-coated copper powders, and has good versatility. The prepared spherical or flaky silver-coated copper powders have good coating properties and good performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the spherical silver-coated copper powder prepared in Example 1 of the present invention;
[0031] Figure 2 This is a surface scanning elemental analysis diagram of the spherical silver-coated copper powder prepared in Example 1 of the present invention.
[0032] Figure 3 This is a scanning electron microscope image of the spherical silver-coated copper powder prepared in Comparative Example 1 of the present invention.
[0033] Figure 4 This is a scanning electron microscope image of the spherical silver-coated copper powder prepared in Example 2 of the present invention.
[0034] Figure 5 This is a surface scanning elemental analysis diagram of the spherical silver-coated copper powder prepared in Example 2 of the present invention.
[0035] Figure 6 This is a surface scanning elemental analysis diagram of the spherical silver-coated copper powder prepared in Comparative Example 2 of the present invention.
[0036] Figure 7 This is a scanning electron microscope image of the flaky silver-coated copper powder prepared in Example 3 of the present invention.
[0037] Figure 8 This is a surface scanning elemental analysis diagram of the flaky silver-coated copper powder prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with specific embodiments.
[0039] In the examples and comparative examples of the present invention, chemical reagents not specified were all commercially available analytically pure for experiments.
[0040] Example 1
[0041] (1) Preparing a copper micron particle dispersion solution: Weighing α-cyclodextrin, copper sulfate, and ascorbic acid according to a molar ratio of α-cyclodextrin: copper sulfate: ascorbic acid = 1:10:10, and dissolving α-cyclodextrin, copper sulfate, and ascorbic acid in 100 ml of deionized water, respectively, to obtain an α-cyclodextrin solution, a copper sulfate solution, and an ascorbic acid solution; pouring the copper sulfate solution into the α-cyclodextrin solution at 90° C., and then stirring for 20 minutes, and then adding the ascorbic acid solution, and reacting for 0.5 hours to obtain a copper micron particle stock solution; centrifuging the copper micron particle stock solution to obtain copper micron particles, washing the copper micron particles with deionized water for multiple times, and then dispersing the copper micron particles in an ethanol solution to obtain a copper micron particle dispersion solution with a concentration of 0.0025 g / ml.
[0042] (2) Take 0.7 g of L-glutamic acid and dissolve it in 10 ml of deionized water to prepare an amino acid solution with a molar concentration of 0.476 mol / L.
[0043] (3) Take 0.1 g of AgNO3 and dissolve it in 10 mL of deionized water to prepare a silver nitrate solution with a molar concentration of 0.059 mol / L.
[0044] (4) Mixing the amino acid solution and the silver nitrate solution to obtain a mixed solution, wherein the molar ratio of silver nitrate to amino acid in the mixed solution is 1:8.
[0045] (5) Take 50 mL of Cu micron particle dispersion solution, stir the Cu micron particle dispersion solution at 25° C. to make the Cu micron particle dispersion solution reach 25° C., and then add the Cu micron particle dispersion solution to the mixed solution of step (4) at a rate of 200 μL / min (the ratio of the amount of copper micron particle dispersion solution to the amount of silver nitrate is about 3.5:1), keep stirring and temperature unchanged, react for 2 hours, and obtain a silver-coated copper powder stock solution.
[0046] (6) After the silver-coated copper powder stock solution is centrifuged to obtain a solid powder, the copper micron particles are dispersed in an ethanol solution after being washed with deionized water for multiple times, and then the solid powder is dried at a temperature of 60° C. After the solid powder is completely dried, a spherical silver-coated copper powder is obtained.
[0047] The scanning electron microscope (SEM) image and element surface scanning analysis image of the silver-coated copper powder prepared in this embodiment are shown as follows: Figure 1 and Figure 2 As shown. Figure 1 , Figure 2It can be seen that the size of the spherical silver-coated copper powder prepared in this embodiment ranges from 2 to 3 μm, the overall size of the product is uniform, well dispersed, and the silver layer is densely coated.
[0048] Comparative Example 1
[0049] In this comparative example, the spherical silver-coated copper powder was prepared by the same method as in Example 1, except that no amino acid was added in this comparative example, and the silver nitrate solution was directly poured into the copper micron particle dispersion for reaction.
[0050] The scanning electron microscope (SEM) image of the silver-coated copper powder prepared in this comparative example is as follows: Figure 3 As shown. Figure 3 It can be seen that when no amino acid is used as an additive, the silver-coated copper powder prepared in this comparative example agglomerates. + It precipitates in the form of silver particles and adheres to the copper particles, and the coating is sparse.
[0051] When the silver nitrate solution and the amino acid solution are mixed, the central silver ion is coordinated by the carboxyl group of the amino acid to form a silver ammonia precursor. When the silver ammonia solution is injected into the copper dispersion, the silver ammonia complex is rapidly adsorbed on the copper powder due to electrostatic energy and van der Waals force, and the amino group of the amino acid further complexes with the surface of the copper powder, thereby the amino acid plays a complexing role.
[0052] As the reaction proceeds, the adsorption of silver ammonia complex increases. At the silver ammonia / copper interface, silver ions begin to migrate to the electrons released from the surface of copper powder. + Reduced to metallic Ag 0 , deposited on the surface of copper powder, and formed Ag nanoseeds on the surface of copper powder, which served as active sites for subsequent growth. At the same time, as the reaction proceeds, Cu atoms continue to turn into Cu 2+ ions migrate into the solution, and the generated silver nanoseeds completely coat the copper surface. The electric displacement reaction between Ag and Cu atoms is self-limited, preventing the copper particles from dissolving and forming a rough or hollow Ag shell. After the electric displacement reaction between Ag and Cu atoms is self-limited, the carboxyl group in the amino acid acts as a reducing agent to slowly reduce the silver ions in the silver ammonia, and the generated silver atoms grow epitaxially on the Ag nanoseeds, thereby forming a dense silver layer. As a result, the amino acid fully exerts its complexing, dispersing, and reducing effects, so that the final preparation is a silver-coated copper powder with dense and uniform coating, appropriate coating thickness, and good dispersibility.
[0053] Since comparative example 1 lacks amino acids, the amino acids cannot play the role of complexation, dispersion, reduction, etc. during the preparation process, resulting in agglomeration of the silver-coated copper powder and a sparse coating layer.
[0054] Example 2
[0055] (1) Preparing a copper micron particle dispersion solution: Weighing α-cyclodextrin, copper sulfate, and ascorbic acid according to a molar ratio of α-cyclodextrin: copper sulfate: ascorbic acid = 1:5:10, dissolving α-cyclodextrin, copper sulfate, and ascorbic acid in 100 ml of deionized water, respectively, to obtain an α-cyclodextrin solution, a copper sulfate solution, and an ascorbic acid solution; pouring the copper sulfate solution into the α-cyclodextrin solution at 60° C., and then stirring for 15 min, and then adding the ascorbic acid solution, and reacting for 1 h to obtain a copper micron particle stock solution; centrifuging the copper micron particle stock solution to obtain copper micron particles, washing the copper micron particles with deionized water for multiple times, and then dispersing the copper micron particles in an ethanol solution to obtain a copper micron particle dispersion solution with a concentration of 0.0025 g / ml.
[0056] (2) Take 0.01 g of glycine and dissolve it in 5 ml of deionized water to prepare an amino acid solution with a molar concentration of 0.027 mol / L.
[0057] (3) Take 0.045 g of AgNO3 and dissolve it in 5 mL of deionized water to prepare a silver nitrate solution with a molar concentration of 0.054 mol / L.
[0058] (4) Mixing the amino acid solution and the silver nitrate solution to obtain a mixed solution, wherein the molar ratio of silver nitrate to amino acid in the mixed solution is 2:1.
[0059] (5) Take 50 mL of Cu micron particle dispersion solution, stir the Cu micron particle dispersion solution at 10° C. to make the Cu micron particle dispersion solution reach 10° C., then add the Cu micron particle dispersion solution to the mixed solution of step (4) at a rate of 300 μL / min (the ratio of the amount of copper micron particle dispersion solution to the amount of silver nitrate is 7:1), keep stirring and temperature unchanged, react for 4 hours, and obtain a silver-coated copper powder stock solution.
[0060] (6) After the silver-coated copper powder stock solution is centrifuged to obtain a solid powder, the copper micron particles are dispersed in an ethanol solution after being washed with deionized water for multiple times, and then the solid powder is dried at 60° C. After the solid powder is completely dried, a spherical silver-coated copper powder is obtained.
[0061] The scanning electron microscope (SEM) image and element surface scanning analysis image of the silver-coated copper powder prepared in this embodiment are shown as follows: Figure 4 and Figure 5 As shown. Figure 4 , 5 It can be seen that the size range of the silver-coated copper powder prepared in this embodiment is 2-4 μm, the overall size of the product is uniform, the dispersion is good, and it still has good coating at a low silver content.
[0062] Comparative Example 2
[0063] This comparative example adopts the same method as Example 2 to prepare spherical silver-coated copper powder, except that: in this comparative example, the amino acid solution is first added to the copper micron particle dispersion solution, and then the silver nitrate solution is added to the copper micron particle dispersion solution, without first mixing the amino acid solution and the silver nitrate solution.
[0064] The element surface scanning analysis diagram of the silver-coated copper powder prepared in this comparative example is as follows Figure 6 As shown. Figure 6 It can be seen that the size range of the silver-coated copper powder prepared in this comparative example is 2-4 μm, the product is well dispersed, but the silver layer is not uniformly coated, and some copper particles are corroded.
[0065] The amino acid added in Comparative Example 2 has a dispersing effect, so that the product is well dispersed. However, when the amino acid solution is directly added to the copper micron particle dispersion, some amino acids are first adsorbed on the surface of the copper particles due to some weak interactions, such as electrostatic effects, van der Waals forces, and atomic interactions. After the addition of silver nitrate copper solution, the complexation of amino acids and silver ions is weakened, and some silver ions will directly nucleate and accumulate on the surface of the copper particles in the solution before complexation, resulting in uneven silver layer coating. In addition, the uncomplexed silver ions will also undergo an galvanic replacement reaction with the surface of the copper micron particles, causing corrosion of the copper particles.
[0066] Example 3
[0067] (1) Preparing a copper microsheet dispersion solution: Weighing octadecylamine, copper bromide and glucose in a molar ratio of octadecylamine: copper bromide: glucose = 4:1:1, dissolving octadecylamine, copper bromide and glucose in 200 ml, 50 ml and 50 ml of deionized water, respectively, to obtain an octadecylamine solution, a copper bromide solution and a glucose solution; stirring the octadecylamine solution at 70°C to form a white emulsion, then adding copper bromide to the white emulsion and stirring for 0.5 h, adding the glucose solution and continuing to stir to form a blue emulsion; transferring the blue emulsion to a stainless steel autoclave lined with polytetrafluoroethylene, reacting at 130°C for 8 h to obtain copper microsheets, washing the copper microsheets with a mixed liquid of water and ethanol, and then adding the copper microsheets to ethanol to obtain a copper microsheet dispersion solution with a concentration of 0.001 g / ml.
[0068] (2) Take 0.06 g of valine and dissolve it in 10 ml of deionized water to prepare an amino acid solution with a molar concentration of 0.0512 mol / L.
[0069] (3) Take 0.03 g of AgNO3 and dissolve it in 10 mL of deionized water to prepare a silver nitrate solution with a molar concentration of 0.0176 mol / L.
[0070] (4) Mixing the amino acid solution and the silver nitrate solution to obtain a mixed solution, wherein the molar ratio of silver nitrate to amino acid in the mixed solution is 1:3.
[0071] (5) Take 50 mL of Cu micron flakes dispersion solution, stir the Cu micron flakes dispersion solution at 40°C to make the Cu micron flakes dispersion solution reach 40°C, and then add the Cu micron flakes dispersion solution to the mixed solution of step (4) at a rate of 1000 μL / min (the ratio of the amount of copper micron flakes dispersion solution to the amount of silver nitrate is about 4.5:1), keep stirring and temperature unchanged, react for 0.5h, and obtain silver-coated copper powder stock solution.
[0072] (6) After the silver-coated copper powder stock solution is centrifuged to obtain a solid powder, the copper micron particles are dispersed in an ethanol solution after being washed with deionized water for multiple times, and then the solid powder is dried at a temperature of 60° C. After the solid powder is completely dried, a flaky silver-coated copper powder is obtained.
[0073] The scanning electron microscope (SEM) image and element surface scanning analysis image of the flaky silver-coated copper powder prepared in this embodiment are shown as follows: Figure 7 and Figure 8 As shown. Figure 7 , 8 It can be seen that the present embodiment prepared the flaky silver-coated copper powder with regular size and uniform coating.
[0074] Example 4
[0075] (1) Preparing a copper micron particle dispersion solution: Weighing α-cyclodextrin, copper sulfate, and ascorbic acid according to a molar ratio of α-cyclodextrin: copper sulfate: ascorbic acid = 1:20:20, and dissolving α-cyclodextrin, copper sulfate, and ascorbic acid in 100 ml of deionized water, respectively, to obtain an α-cyclodextrin solution, a copper sulfate solution, and an ascorbic acid solution; pouring the copper sulfate solution into the α-cyclodextrin solution at 80° C., and then stirring for 17 minutes, and then adding the ascorbic acid solution, and reacting for 2 hours to obtain a copper micron particle stock solution; centrifuging the copper micron particle stock solution to obtain copper micron particles, washing the copper micron flakes with a mixed liquid of water and ethanol, and then adding the copper micron particles to ethanol to obtain a copper micron particle dispersion solution with a concentration of 0.002 g / ml.
[0076] (2) Take 0.045 g of L-alanine and dissolve it in 5 ml of deionized water to prepare an amino acid solution with a molar concentration of 0.100 mol / L.
[0077] (3) Take 0.02 g of AgNO3 and dissolve it in 5 mL of deionized water to prepare a silver nitrate solution with a molar concentration of 0.020 mol / l.
[0078] (4) Mixing the amino acid solution and the silver nitrate solution to obtain a mixed solution, wherein the molar ratio of silver nitrate to amino acid in the mixed solution is 1:5.
[0079] (5) Take 40 mL of Cu micron particle dispersion solution, stir the Cu micron particle dispersion solution at 25° C. to make the Cu micron particle dispersion solution reach 25° C., and then add the Cu micron particle dispersion solution to the mixed solution of step (4) at a rate of 500 μL / min (the ratio of the amount of copper micron particle dispersion solution to the amount of silver nitrate is about 8.7:1), keep stirring and temperature unchanged, react for 1 hour, and obtain a silver-coated copper powder stock solution.
[0080] (6) After the silver-coated copper powder stock solution is centrifuged to obtain a solid powder, the copper micron particles are dispersed in an ethanol solution after being washed with deionized water for multiple times, and then the solid powder is dried at 60° C. After the solid powder is completely dried, a spherical silver-coated copper powder is obtained.
[0081] The spherical silver-coated copper powder prepared in this example has similar structure and performance to the spherical silver-coated copper powder prepared in Example 1.
[0082] Example 5
[0083] This embodiment adopts the same method as that of Embodiment 3 to prepare flaky silver-coated copper powder, except that: in the process of preparing the copper micron sheet dispersion solution, octadecylamine, copper bromide and glucose are weighed according to a molar ratio of octadecylamine: copper bromide: glucose = 1:1:1, and the octadecylamine solution is stirred at 60°C; after reacting at 120°C for 10 hours, the copper micron sheets are obtained.
[0084] The flaky silver-coated copper powder prepared in this example has similar structure and properties to the flaky silver-coated copper powder prepared in Example 3.
[0085] Example 6
[0086] This embodiment adopts the same method as that of Embodiment 3 to prepare flaky silver-coated copper powder, except that: in the process of preparing the copper micron sheet dispersion solution, octadecylamine, copper bromide and glucose are weighed according to a molar ratio of octadecylamine: copper bromide: glucose = 5:2:1, and the octadecylamine solution is stirred at 50°C; after reacting at 100°C for 20 hours, the copper micron sheets are obtained.
[0087] The flaky silver-coated copper powder prepared in this example has similar structure and properties to the flaky silver-coated copper powder prepared in Example 3.
[0088] In summary, in the preparation process of the present invention, only one additive, amino acid, needs to be added to prepare spherical and flaky silver-coated copper powders with dense and uniform coating, appropriate coating thickness and good dispersibility, without the need to add other additives separately, which effectively reduces the amount of additives used, and is beneficial to improving the safety and environmental protection of the preparation process. At the same time, in the preparation process of the present invention, the process flow is simple, does not involve high temperature, gas protection and other processes, and is helpful to reduce the energy consumption of preparation. Therefore, the preparation method of the present invention has the characteristics of simplicity, high efficiency, green environmental protection, low cost and the like, and is suitable for industrial promotion and application.
[0089] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing spherical and flaky silver-coated copper powder, characterized in that: The preparation method comprises the following steps: (1) mixing an amino acid solution and a silver nitrate solution to obtain a mixed solution; (2) firstly placing the copper micron particle dispersion solution or the copper micron flake dispersion solution under reaction temperature conditions and stirring the solution to make the copper micron particle dispersion solution or the copper micron flake dispersion solution reach the reaction temperature, keeping stirring and the temperature constant, then adding the mixed solution to the copper micron particle dispersion solution or the copper micron flake dispersion solution, reacting for a period of time, and obtaining a silver-coated copper powder stock solution; (3) After the silver-coated copper powder stock solution is centrifuged, a solid powder is obtained, and after the solid powder is washed and dried, the silver-coated copper powder is obtained.
2. The method for preparing spherical and flaky silver-coated copper powder according to claim 1, characterized in that: In the step (2), the reaction temperature is 10 to 40° C. and the reaction time is 0.5 to 4 hours.
3. The method for preparing spherical and flaky silver-coated copper powder according to claim 1, characterized in that: In the step (2), the rate of adding the mixed solution is 200 to 1000 μl / min.
4. The method for preparing spherical and flaky silver-coated copper powder according to claim 1, characterized in that: The amino acids include one or more of glycine, L-alanine, L-glutamic acid and valine.
5. A method for preparing spherical or flaky silver-coated copper powder according to claim 1 or 4, characterized in that: The molar concentration of the amino acid solution is 0.01-0.5 mol / L.
6. The method for preparing spherical and flaky silver-coated copper powder according to claim 1, characterized in that: The molar concentration of the silver nitrate solution is 0.01-0.1 mol / L.
7. The method for preparing spherical and flaky silver-coated copper powder according to claim 1, characterized in that: In the step (1), the molar ratio of silver nitrate to amino acid in the mixed solution is 1:8 to 2:
1.
8. A method for preparing spherical or flaky silver-coated copper powder according to any one of claims 1, 6 and 7, characterized in that: In the step (2), the ratio of the amount of the copper micron particle dispersion solution or the copper micron flake dispersion solution to the amount of silver nitrate is 3.5:1 to 9:
1.
9. The method for preparing spherical and flaky silver-coated copper powder according to claim 1, characterized in that: The specific preparation method of the copper micron particle dispersion solution is as follows: α-cyclodextrin, copper sulfate, and ascorbic acid are weighed according to a molar ratio of α-cyclodextrin: copper sulfate: ascorbic acid = 1:20:20 to 1:5:10, and α-cyclodextrin, copper sulfate, and ascorbic acid are respectively dissolved in deionized water to obtain an α-cyclodextrin solution, a copper sulfate solution, and an ascorbic acid solution; the copper sulfate solution is poured into the α-cyclodextrin solution at 60 to 90° C., and then stirred for 15 to 20 minutes, and then the ascorbic acid solution is added, and after reacting for 0.5 to 2 hours, a copper micron particle stock solution is obtained; the copper micron particle stock solution is centrifuged to obtain copper micron particles, and after washing the copper micron particles, the copper micron particles are added into ethanol to obtain a copper micron particle dispersion solution; The specific preparation method of the copper microsheet dispersion solution is as follows: octadecylamine, copper bromide and glucose are weighed according to a molar ratio of octadecylamine: copper bromide: glucose = 1:1:1 to 5:2:1, and octadecylamine, copper bromide and glucose are respectively dissolved in deionized water to obtain octadecylamine solution, copper bromide solution and glucose solution; the octadecylamine solution is stirred at 50 to 70° C. to form a white emulsion, and then copper bromide is added to the white emulsion, and after continuous stirring for 0.5 h, the glucose solution is added, and continuous stirring is continued to form a blue emulsion; The blue emulsion is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and reacted at 100-130°C for 8-20 hours to obtain copper microsheets. After washing the copper microsheets, the copper microsheets are added to ethanol to obtain a copper microsheet dispersion solution.
10. A method for preparing spherical or flaky silver-coated copper powder according to any one of claims 1, 2, 3, 4, 6, 7, and 9, characterized in that: The amino acid solution is prepared by dissolving amino acids in deionized water; and the silver nitrate solution is prepared by dissolving silver nitrate in deionized water.